2014
DOI: 10.1007/s40685-014-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

On the sunk-cost effect in economic decision-making: a meta-analytic review

Abstract: Although the effect of monetary sunk costs on decision-making is widely discussed, research is still fragmented, and results are sometimes controversial. One reason for this incomplete picture is the missing differentiation between the effect of sunk costs on utilization and progress decisions and its respective moderators. This article presents the results of a meta-analytic review of 98 effect sizes of the sunk-cost effect, with special emphasis on the decision-specific influence of moderators. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 86 publications
1
55
0
1
Order By: Relevance
“…In this situation, when starting to execute planning, sometimes it is verified that things do not happen as imagined, as the investments in research and development, and in the brand promotions (Roth, Robbert, & Straus, 2014;Hong, Huang, & Zhao, 2018). This is the moment when the individual questions whether to proceed or abandon the planning (Schulz-Hardt, Vogelgesang, Pfeiffer, & Thurow-Kröning, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, when starting to execute planning, sometimes it is verified that things do not happen as imagined, as the investments in research and development, and in the brand promotions (Roth, Robbert, & Straus, 2014;Hong, Huang, & Zhao, 2018). This is the moment when the individual questions whether to proceed or abandon the planning (Schulz-Hardt, Vogelgesang, Pfeiffer, & Thurow-Kröning, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nessa situação, ao iniciar a execução de um planejamento, por vezes, constata-se que as coisas não acontecem conforme imaginado, a exemplo dos investimentos em pesquisa e desenvolvimento e na promoção de marcas (Roth, Robbert, & Straus, 2014;Hong, Huang, & Zhao, 2018). Este é o momento no qual há o questionamento se o indivíduo deve prosseguir ou desistir do plano (Schulz-Hardt, Vogelgesang, Pfeiffer, & Thurow-Kröning, 2009).…”
Section: Introductionunclassified
“…The first is described as “utilization decision,” a decision wherein the decision maker has to choose between two equal alternatives. Roth et al (2015) illustrated this type of decision with the example of a person who purchased a ticket to a play at the local theater but later gets invited by a good friend to a special Italian dinner. Even when the person prefers attending the dinner, he/she thinks about the sunk cost already paid for the ticket and decides to go to the play.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences in economics do not help to sustain the sunk-cost effect. A meta-analysis by Roth et al (2015), which involved solely monetary sunk-cost decisions, revealed that an economic background on the part of the participants does not have a significant influence on utilization decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation